Manganese accumulates in the brain of northern quolls (Dasyurus hallucatus) living near an active mine. (February 2018) - Amir Abdul Nasir, Ami Fadhillah; Cameron, Skye F.; von Hippel, Frank A.; Postlethwait, John; Niehaus, Amanda C.; Blomberg, Simon; Wilson, Robbie S.
Abstract: Mining is fundamental to the Australian economy, yet little is known about how potential contaminants bioaccumulate and affect wildlife living near active mining sites. Here, we show using air sampling that fine manganese dust within the respirable size range is found at levels exceeding international recommendations even 20 km from manganese extraction, processing, and storage facilities on Groote Eylandt, Northern Territory. Endangered northern quolls ( Dasyurus hallucatus ) living near mining sites were found to have elevated manganese concentrations within their hair, testes, and in two brain regions—the neocortex and cerebellum, which are responsible for sensory perception and motor function, respectively. Accumulation in these organs has been associated with adverse reproductive and neurological effects in other species and could affect the long-term population viability of northern quolls. Graphical abstract: Image 1 Highlights: We measured the accumulation of manganese (Mn) dust in the hair and organs of wild quolls living near an active mine. Levels of respirable Mn exceeded recommendations for non-occupational exposure even 20 km from mining facilities. Quolls living near mining facilities had 2x to 3x more Mn in their neocortex and cerebellum, respectively. Accumulation of Mn in the testes could affect the reproductive success of suicidally breeding male quolls. We encourage more studies in wild ecosystems, particularly when the effects of mining can still be mitigated. Abstract : Wild marsupials living near an active manganese mine accumulate manganese in their brains and testes, where it may impair cognitive or sexual function.